Identification of the novel HLA‐A*24:02:138 allele in a Chinese individual. (16th March 2022) - Chen, Nanying; Fu, Rui; Dong, Lina; He, Ji; Zhu, Faming
Abstract : HLA‐A*24:02:138 differs from HLA‐A*24:02:01:01 by one nucleotide substitution at position 549 C>T.